Cambios dimensionales de los arcos dentales en niños de 3 a 12 años de edad de la ciudad de Medellín. Estudio longitudinal- reporte preliminar - Mariaca-de Botero, Libbe; Téllez-A., Yezid; Mejía-M., Juan Fernando; Giraldo-C., Gloria María (Revista Facultad de Odontología Universidad de Antioquia, 2016)
This is a preliminary report (4 years) of an eight years longitudinal study. These results were obtained from 74 children: 24 boys and 50 girls, all of them starting at 3 to 5 years of age and follow up to the age of 9years. The purpose of this invesksradon was to fmd out the change in length, width and circumference of the dental arches in children through out their p.hisiologic dental growth and development. Crowding- has been one of the most common and difficult problem to be solved during the children occlusal development, We want with this investigation to learn more about the behavior of the growth and development of the dental arches, in order to decide in between early or late approach of crowding. Impression of dental arches were taken every six months on each patient and dental casts were obtained from the impressions. Arch length, arch width and arch circumference were measured in both upper and lower models of each patient. ,Arch lenght and arch width were measured with a digital microscope and arch circumference with a modified catenometer, both a high precision. At this moment of the research the results showed a statistical significant increment in all measurements when they were compared with the baseline measurements as the children advance in their dental and chronological age. As a general trend when sex variable were matched, boys showed a greater increase in all dimensions than girls. These results are similar to those obtained by- Moorrees (1) in 1959.